Disordered brownmillerite Ba2InCeO5+delta with enhanced oxygen reduction activity - Jijil, Chamundi P.; Unni, SreeKuttan M.; Sreekumar, Kurungot; Devi, R. Nandini (Chemistry of Materials, 2012)
A disordered brownmillerite, Ba2InCeO5+delta, with slight tetragonal distortion from ideal cubic perovskite is synthesized and its oxygen reduction reactivity tested. The material displayed oxygen reduction behavior in alkaline solution comparable to that of standard 40 wt % Pt/C catalyst and attractive activity characteristics which renders it a potential system for low temperature fuel cell applications.
Keywords: brownmillerite; fuel cell; oxygen reduction reaction; Rietveld refinement

Effect of b site coordination environment in the ORR activity in disordered brownmillerites Ba2In2-xCexO5+delta - Jijil, Chamundi P.; Bhange, Siddheshwar N.; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2015)
Ba2In2O5 brownmillerites in which the In site is progressively doped with Ce exhibit excellent oxygen reduction activity under alkaline conditions. Ce doping leads to structural changes advantageous for the reaction. Twenty-five percent doping retains the ordered structure of brownmillerite with alternate layers of tetrahedra and octahedra, whereas further increase in Ce concentration creates disorder. Structures with disordered oxygen atoms/vacancies are found to be better oxygen reduction reaction catalysts probably aided by isotropic ionic conduction, and Ba2In0.5Ce1.5O5+delta is the most active. This enhanced activity is correlated to the more symmetric Ce site coordination environment in this compound. Stoichiometric perovskite BaCeO3 with the highest concentration of Ce shows very poor activity emphasizing the importance of oxygen vacancies, which facilitate O-2 adsorption, in tandem with catalytic sites in oxygen reduction reactions.
Keywords: brownmillerite; fuel cell; oxygen disorder; oxygen reduction reaction; Rietveld refinement

Tuning of oxygen reduction pathways through structural variation in transition metal-doped Ba2In2O5 - Thundiyil, Shibin; Pandikassala, Ajmal; Kurungot, Sreekumar; Devi, R. Nandini (ChemElectroChem, 2022)
Abstract Oxygen reduction reaction (ORR) can take place either through a two-electron pathway to form H2O2 or through a four-electron pathway to form H2O. Both the reactions are important in the respective fields, viz., H2O2 production as well as fuel cell technology, and rational design of catalysts is mandatory to acquire high energy efficiency in both cases. Here, we report the structure-electrochemical property correlation of a series of perovskite related brownmillerite compounds, Ba2In0.75M0.25O5 (M=Mn/Fe/Co/Ni/Cu), synthesized by solid-state method. On transition metal doping, octahedral distortions were observed, and the highly disordered material tends to follow the 4e transfer mechanism. More symmetrical structures followed the 2e pathway to form H2O2 as the product with high peroxide selectivity. The distortion in the octahedral arrangement can be a descriptor to finetune the selectivity of the catalysts towards the 2e and 4e pathways of ORR.
Keywords: brownmillerite; Descriptors; Electrochemical H2O2 synthesis; Octahedral distortion; oxygen reduction reaction